The Effect of Fintech Adoption, Financial Literacy and Financial Management Behavior to MSME Performance in Medan - Amaliani, Fitri; Muliyani, Muliyani (SEIKO : Journal of Management & Business, 2024)
This study aims to analyze the influence of fintech, financial literacy and financial management behavior on MSME performance. This study used a quantitative research design using statistical testing methods based on statistical tests.Data collection is carried out through the distribution of offline and online questionnaires to MSME players who use fintech payment methods in the form of "QRIS" spread across the Medan City area. The population in this study is all MSME actors who use the Qris application with samples selected using random sampling techniques. The number of samples used was 44 people. This study shows the following results: first, fintech has a positive effect and significance on MSME performance.second, financial literacy has a positive effect and significance on MSME performance.third, financial management behavior has no influence on MSME performance then the hypothesis.